Mikrobna biotehnologija: skripta z navodili za vaje za študijski program Biologija - Trček, Janja (2018)
Microbial Biotechnology: Instructions for Study Program Biology. Microbial biotechnology - theoretical basics with instructions for practical exercises is aimed for students of the undergraduate university programme Biology. It is composed of theoretical part which presents basic tools and methods used in microbial biotechnology and eight laboratory exercises. In the first four practical exercises the students learn about laboratory bioprocesses by using different microorganism for the production of useful products. In the second part the students are involved in genetic engineering, get into basics of bioinformatics and learn methods used in molecular cloning of bacteria. By performing and understanding these exercises the students are introduced into the field of microbial biotechnology.
Keywords: microbial biotechnology; instructions for practical exercises; microbial bioprocess; bioinformatics; cloning